2020
DOI: 10.1111/jai.14067
|View full text |Cite
|
Sign up to set email alerts
|

Fort Peck paddlefish population survival and abundance in the Missouri River

Abstract: Excessive fishing pressure can induce population declines or complete collapse of fisheries. Unless commercial and recreational fisheries for K‐selected fishes, or those with slow growth and late maturation, are carefully managed, declines in abundance or fishery collapse is probable. Paddlefish Polyodon spathula,are a K‐selected species that experienced historical declines in abundance as a result of habitat degradation and overfishing. Mark‐recapture studies are well‐suited for long‐lived fishes by providing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
(57 reference statements)
1
6
0
Order By: Relevance
“…The low total annual mortality rates observed in this study (A = 15% for males and 12% for females, including harvest) are very similar to the low rates for the stock estimated from jaw tag recoveries (18% for males and 8% for females; Glassic et al 2020). In both studies, females had higher survival.…”
Section: Mortality Ratessupporting
confidence: 82%
See 4 more Smart Citations
“…The low total annual mortality rates observed in this study (A = 15% for males and 12% for females, including harvest) are very similar to the low rates for the stock estimated from jaw tag recoveries (18% for males and 8% for females; Glassic et al 2020). In both studies, females had higher survival.…”
Section: Mortality Ratessupporting
confidence: 82%
“…DEMOGRAPHICS OF AN ISOLATED PADDLEFISH STOCK TABLE 1. Age (years) summary for harvested Paddlefish of the Fort Peck stock, Montana, 1992-2020. Data were not collected in 1997, 1999, 2001, 2003 Von Bertalanffy growth curves indicated that females were much larger than males over comparable ages in terms of BL (Figure 5) and weight (Figure 6).…”
Section: Age and Growthmentioning
confidence: 99%
See 3 more Smart Citations